Outcome of Postpartum Intrauterine Contraceptive Device Insertion: Findings of an Institution Based Crosssectional Study - Farjana, Sharmin; Ivy, Rokshana; Nessa, Khaledun (Journal of Preventive and Social Medicine, 2021)
Background: To foster family planning activities by postpartum IUCD insertion, side effects and complications of PPIUCD insertion need to be characterized. The study was conducted to find out the outcomes of postpartum intrauterine contraceptive device insertion among women attending a tertiary level hospital. Methods: A cross sectional study was conducted among 130 women. Data were collected by face-to-face interview and reviewing medical records with semi- structured questionnaire and checklist. The subjects were purposively selected following specific selection criteria and maintaining ethical issues. The study was conducted during the period from October 2016- March 2017 in a tertiary hospital: Shaheed Suhrawardy Medical College Hospital (ShSMCH), Dhaka. Results: The study revealed that majority (53.1%) of women were 25-30 years and the mean (±SD) age was 26.40±4.273 years. Around 26.2% had secondary education and most of them i.e. 60.8% were housewife. Study revealed that average monthly family income was Tk. 20815.38 ± 9097.904. Majority (90%) of women choose PPIUD because it is convenient. Most of the respondents were inserted immediately after delivery within 10 minutes. Intracaesarean and manual insertion of PPIUCD was practiced in majority i.e. 79(60.8%) of the respondents. The study revealed that three fourth of the respondents had no side effect while common side effects of PPIUCD included vaginal discharge (12.3%), thread coming out (14.6%), missing thread (13.8%), lower abdominal pain (16.2%), expulsion (6.2%) and coital discomfort (10.8%). Only 18.5% respondents had abnormal uterine bleeding and 6.2% had PID. The results show expulsion rate was more in vaginal route (11.8%) than intra-caesarean route (2.5%) and this difference was statistically significant (p<0.05). All complications like abnormal uterine bleeding (15.7%) and PID (20.3%) were seen more in vaginal insertions as compared to insertion during caesarean section and was statistically significant (p<0.05). Conclusion: To reduce the unwanted pregnancy in postpartum period and maternal and child mortality and morbidity, PPIUCD insertion along its continuation by overcoming side effects and complications is an earnest need in a densely populated country like Bangladesh. JOPSOM 2020; 39(2): 1-7